Long Run Growth in Haiti - Cicowiez, Martín (2018)
In this paper, we first assess the historical evolution of total factor productivity in Haiti and then consider alternative scenarios related to accelerating growth. Specifically, we focus on issues of intertemporal coordination between population growth, TFP (Total Factor Productivity), capital accumulation, foreign debt, output, and consumption. To that end, we developed a model of the Ramsey-Cass-Koopmans type. This class of models are the workhorse of most contemporary work in modeling the long and very long term growth of countries (Barro and Sala-i-Martin 2004 and Acemoglu 2009). In doing so, we make two contributions to the empirical economic analysis of developing countries such as Haiti: (a) we estimate Haiti’s capital stock and perform a growth accounting exercises using data that goes back to the 1950s; and (b) we built a 2016 macro consistent dataset and use it to calibrate a long-run growth model for a small open economy such as Haiti.